Analysis Of Local Msme Development Strategy "Vis A Vis" The Development Of National Chain Minimarket Retail In Palembang City - M. Iqbal; Citra Pertiwi; Abubakar Sidik; Yusiresita Pajaria (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The phenomenon of the proliferation of National Chain Minimarket Retail Groups has become a scourge for local MSMEs in Indonesia. Although the government continues to provide space for local MSMEs through Permendagri No. 53/M-DAG/PER/12/2008 which requires the establishment of minimarkets to pay attention to the existence of traditional markets and smaller neighborhood stalls/shops. However, some regions are actually utilizing the momentum of the existence of modern minimarkets, one of which is Yogyakarta through the Mayor's Regulation which issued a policy so that the national chain minimarket retail group empowers local MSMEs and is given a special place to market local products. Palembang, which is known for its pempek as a culinary specialty, has enormous potential for the development of local MSMEs, but MSME players who become industry players are still not ideal. This study aims to analyze how the development strategy of Local MSMEs "vis a vis" the massive development of national chain minimarket retail in Palembang City. This research uses a mixed method approach, which consists of two approaches, namely quantitative and qualitative. Mixed methods used are descriptive qualitative using SWOT analysis (strengths, weaknesses, opportunities, threats) to analyze the development strategy of local MSMEs in Palembang City. As well as quantitative descriptive using the IFAS and EFAS matrix to calculate the weighting, rating, and formulation of the development strategy position of Local MSMEs in Palembang City. The results of this study indicate that based on the results of the SWOT diagram analysis, the X and Y axes are obtained. The straight line in the diagram above shows the coordinates in quadrant 1 position. Quadrant 1 is a very favorable situation, where local wisdom MSME players can have strengths and opportunities that can be utilized so that it is suitable to use the SO (strength-opportunity) strategy to develop local wisdom MSME businesses supported by aggressive growth strategies, namely 1) Maintaining Public Interest by Optimizing Support Programs from the Government; 2) Optimizing Sales Without Limiting Target Markets both domestically and abroad; 3) Utilizing Community Expertise to Intervene Local Products to National Chain Minimarkets; and Creating Training Programs from the Association of Local Culinary Business Groups to Maintain the Authentic Taste of Products.